Severe Dementia Predicts Weight Loss by the Time of Death - Ciciliati, Aline Maria M.; Adriazola, Izabela Ono; Souza Farias-Itao, Daniela; Pasqualucci, Carlos Augusto; Leite, Renata Elaine Paraizo; Nitrini, Ricardo; Grinberg, Lea T.; Jacob-Filho, Wilson; Suemoto, Claudia Kimie (Frontiers in Neurology, 2021)
BACKGROUND: Body mass index (BMI) in midlife is associated with dementia. However, the association between BMI and late-life obesity is controversial. Besides, few studies have investigated the association between BMI and cognitive performance near the time of death, considering information on the cause of death confirmed by an autopsy examination. We aimed to investigate the association between BMI and dementia in deceased individuals who underwent a full-body autopsy examination. METHODS: Weight and height were measured before the autopsy exam. Cognitive function before death was investigated using the Clinical Dementia Rating (CDR) scale, and dementia was considered when the CDR was ≥ 1. The cross-sectional association between BMI and dementia was investigated using linear regression adjusted for sociodemographic and clinical variables. RESULTS: We included 1,090 individuals (mean age 69.5±13.5 years old, 45.5% women). Most participants (56%) had normal BMI (18.5-24.9 kg/m²), the prevalence of dementia was 16%. 24% of the sample had cancer, including 76 cases diagnosed only by the autopsy examination. We observed that lower BMI was associated with severe dementia in late life. CONCLUSION: Lower BMI near the event of death was associated with a higher frequency of severe dementia, but we did not find any association with less advanced dementia stages.